CELLULASE PRODUCTION FROM ACTINOMYCETES USING OIL PALM EMPTY FRUIT BUNCH FIBER AS MEDIUM - hamka (Jurnal Loupe, 2014)
Oil palm empty fruit bunch (OPEFB) is a common solid waste from palm oil industry that requires proper handling to be processed into bio-ethanol as new bio-energy source to substitute fossil fuel, oil, gas, and coal. Microbial applications have been considered an effective way to degrade a lignocellulosic biomass into simple sugars as a critical material for bio-ethanol production. It efficacy to degrade cellulose was determined by cellulase production from CMC as medium. Actinomycetes isolate 11.2.A showed high cellulase activity on carboxylmethyl cellulose (CMC) broth. After incubation for 5 days at 30oC, pH 7 and 150 rpm agitation rate the highest cellulase activity generated by the isolate 11.2.A was 0.62 U/ml on CMC as medium. Actinomycetes isolates 11.2.A was proved to be the effective producer of cellulase specific for CMC. The isolate 11.2.A was also selected to be used in liquefaction of OPEFB. Actinomycetes isolate 11.2.A gave a better performance for being able to degrade the OPEFB with cellulase activity at 0.42 U/ml. This microbial and its enzymes should be very useful in the process of turning the solid waste like OPEFB into value products such as reducing sugar, sugar alcohol and bio-ethanol.